Intercultural education and Roma in Croatia - Hrvatić, Neven; Posavec, Koraljka (2000)
Since the begining of their settlements, the Romanies have formed a historically indigenous minority due to their transnational identity (Dubrovnik,1362.). A specific tribal system (family, vitcha - extended family, big vitcha - family association, tribal group) and economic organization have caused dispersion, specialization and the partial loss of their national identity.
The research project "School curriculum and characteristics of Croatian national cultura" through its empirical research on a stratified sample of secondary school students, directed attention to the existing stereotypes towards the Romanies. Futhermore,a low acceptance level of the elements of the Romany culture (language, art, history, sustoms) as well as a high level of social remoteness from Romanies (modified Bogardus scale) have been found, indicating the need for intercultural education for all pupils in Croatia.
The projects and experimental implementation of the Summer School for Romany children in Croatia and the Romany Educational Community are innovative forms of education for Romany children - together with the edition of the Romany bulletin Romano Akharipe - The Romany Voice, and Nevo Drom - The New Way - are the first steps towards a conceptualization oa a Croatian educational model for thr Romanies. The organization of a specific educational system for the Romany people plays an important role in the formation and structuralization of the Romany national community within the intercultural environment in Croatia.
Projekt MZOS
ENG